2016
DOI: 10.1007/s40265-016-0564-5
|View full text |Cite
|
Sign up to set email alerts
|

Nail Psoriasis: A Review of Treatment Options

Abstract: Nail involvement affects 80–90 % of patients with plaque psoriasis, and is even more prevalent in patients with psoriatic arthritis. This review is the result of a systemic approach to the literature and covers topical, intralesional, conventional systemic, and biologic systemic treatments, as well as non-pharmacological treatment options for nail psoriasis. The available evidence suggests that all anti-tumor necrosis factor-α, anti-interleukin (IL)-17, and anti-IL-12/23 antibodies which are available for plaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 159 publications
2
129
0
16
Order By: Relevance
“…In the same study,patients treated with cyclosporine showed a 37% mean improvement in the NAPSI score (21 (25). The efficacy of etanercept in nail psoriasis has also been supported by other studies (7,26,27). In our case, there was a rapid response to etanercept with a significant reduction in the NAPSI score.…”
Section: Case Reportsupporting
confidence: 84%
See 1 more Smart Citation
“…In the same study,patients treated with cyclosporine showed a 37% mean improvement in the NAPSI score (21 (25). The efficacy of etanercept in nail psoriasis has also been supported by other studies (7,26,27). In our case, there was a rapid response to etanercept with a significant reduction in the NAPSI score.…”
Section: Case Reportsupporting
confidence: 84%
“…Nail pitting is the most common sign encountered in nail psoriasis (6)(7)(8). These changes are not specific and may also occur in other disorders (9).…”
Section: Introductionmentioning
confidence: 99%
“…Manifestations were symmetric polyarthritis in more than five joints (fingers, toes, wrists, ankles, knees, elbows and shoulders), with lesions mimicking rheumatoid arthritis. [1][2][3][4] There were also right sternoclavicular arthritis and enthesitis of Achilles tendons. 4 Psoriasis can significantly affect the functional, psychological and social well-being of the patients, causing at least moderate effect on the quality of life in 43.2% of individuals.…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…4 Psoriasis can significantly affect the functional, psychological and social well-being of the patients, causing at least moderate effect on the quality of life in 43.2% of individuals. 3,5 Psoriasis is a chronic inflammatory condition with an estimated prevalence of 0.7 to 8.5%, which often affects extensor areas of the limbs, scalp, umbilicus and lumbar regions. [1][2][3][4][5] The major risk factor of susceptibility to the early onset psoriasis is HLA-Cw6 on chromosome 6; and the cytokines involved in the etiopathogenesis of psoriatic cutaneous alterations are tumor necrosis factor (TNF)-α, interferon (IFN)-γ, interleukin (IL)-2, IL-17A, IL-17F, IL-22, IL-26, IL-23, IL-20, and IL-15.…”
Section: Psoriatic Arthritismentioning
confidence: 99%
See 1 more Smart Citation